2010
DOI: 10.1097/pts.0b013e3181fd1a00
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships Between Hospital Patient Safety Culture and Adverse Events

Abstract: Our findings support the idea that a more positive patient safety culture is associated with fewer adverse events in hospitals. Further research is needed to determine the generalizability of these results to larger sets of hospitals and to examine the causal relationship between patient safety culture and clinical patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
247
6
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(286 citation statements)
references
References 7 publications
13
247
6
7
Order By: Relevance
“…Therefore, by taking a daily diary approach to assess 'perceptions' of daily hassles, we are attempting to capture these differences at the individual level, albeit via self-report. We utilised self-report measures of safety as associations between measures of 'perceptions' of safety (i.e., safety culture) and more objective indicators of safety have been established previously [39][40][41].…”
Section: Contribution Of the Researchmentioning
confidence: 99%
“…Therefore, by taking a daily diary approach to assess 'perceptions' of daily hassles, we are attempting to capture these differences at the individual level, albeit via self-report. We utilised self-report measures of safety as associations between measures of 'perceptions' of safety (i.e., safety culture) and more objective indicators of safety have been established previously [39][40][41].…”
Section: Contribution Of the Researchmentioning
confidence: 99%
“…Related to this is the need for a strong culture of safety, which is a driving force for quality care. Culture of safety has been linked to patient outcomes29 and has been specifically mentioned in the radiation oncology context 5, 24…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous research, the two burnout facets of Emotional Exhaustion and Depersonalisation were included (Halbesleben et al, 2008). Safety perceptions were used to measure patient safety, as previous research has suggested these are associated with objectively measured patient safety outcomes (Hansen et al, 2011, Hofmann and Mark, 2006, Mardon et al, 2010 and are useful for detecting variations in perceived safety between individual practitioners (Halbesleben et al, 2008, Louch et al, 2016. There were two hypotheses: Hypothesis 1: There will be a direct association between depressive symptoms and patient safety perceptions.…”
Section: The Study Aimsmentioning
confidence: 99%